Maqashidi Interpretation Perspective on Coastal Reclamation in Q.S. Al-Nahl [16]: 14 - Muhammad Ilham Sofyan (Indonesia); Taufiq Qomarudin (Mesir); Syarifah Nadhiya (Brunei Darussalam) (IAT IAIN Pontianak, 2023)
In general, the Qur'an explains the practices of utilizing marine areas by means of fishing, collecting pearls, trading, and transportation in Surah Al-Nahl 14. When interpreting this verse, scholars do not impose restrictions on the methods of benefiting from the sea (variability). However, the aspect of preservation from harm must still be fulfilled. Coastal reclamation projects often lead to electoral conflicts, including their impacts on the damage to marine ecosystems and coastal areas. The objective of this research is to understand the Qur'an's response to coastal reclamation practices and the ideal methods for benefiting from the sea. This type of research is a qualitative literature study using the Maqashidi Tafsir method. This methodological approach is suitable because it can explore the dimensions of the ghayah (purpose) and wasilah (means) of specific themes in the Qur'an, making it relevant to address current issues. The research results in the perspective that the Maqashid of Surah Al-Nahl 14 align with coastal reclamation practices but emphasize the need to mitigate their impact to prevent harm to marine and coastal ecosystems. The utilization of the sea is also considered from a protective (min haits al-adam) and productive (min haits al-wujud) perspective.